Cultural Representation in the L'Oréal Paris Advertisement "Nous le valons bien" - Nurfebry Salsabila Isdiansyah; Diah Vitri Widayanti (Jurnal QOSIM : Jurnal Pendidikan, Sosial & Humaniora, 2026)
The expansion of digital media has transformed advertising into a medium that constructs cultural meanings and social values beyond its promotional function. This study aims to analyze cultural representation in the L’Oréal Paris 2024 advertisement “Nous le valons bien”, focusing on how meaning is constructed through visual and verbal elements. The research applies a qualitative descriptive method using a constructionist approach. The data source is a 40 second advertisement video obtained from the official YouTube platform, with scenes and sequences as the unit of analysis. The findings reveal that representation operates through reflective, intentional, and constructionist approaches. While the advertisement reflects multicultural diversity and communicates empowerment, the constructionist approach dominates by actively producing meanings of inclusive beauty, contemporary feminism, and global identity. In conclusion, the advertisement functions as a cultural text that not only reflects but also shapes social reality, contributing to cultural studies and language learning.